How Contrastive Explanation Facilitates Theory Building - Tsang, Eric W. K.; Ellsaesser, Florian (Academy of Management Review, 2011)
We introduce the theory of contrastive explanation, the core argument of which is that we do not explain an entire phenomenon but only aspects of it. Using the example of transaction cost economics, we illustrate how contrastive explanation can assist organizational researchers in creating, broadening, and deepening their theories through posing suitable contrastive questions. We summarize our discussion into eight heuristic rules that will serve as useful theory-building tools.